Solvent-Free Synthesis of Co-Based Zeolitic Imidazolate Framework (ZIF-9) for the Removal of Congo Red from Water - Tran, Khoa Dang; Phan, Hoan Tuan; Nguyen, Chi Thi Kim; Nguyen, Bao Chi; Le, Ha Vu; Nguyen, Khoa Dang (Universitas Gadjah Mada, 2025)
The study presented a green and benign approach via mechanochemistry for rapidly preparing a typical cobalt-based zeolitic imidazolate framework, namely ZIF-9. The structural, morphological and textural properties of the obtained material were confirmed by X-ray diffraction (XRD), scanning electron microscopy (SEM), and nitrogen sorption at 77 K. The prepared material was then employed as an efficient adsorbent to remove Congo red (CR) from the aqueous solution. Intensive experiments were then conducted with the removal of CR to investigate the effect of adsorption conditions, including contacting time, pH value, and initial concentration of organic dye solution. The adsorption process follows the pseudo-second-order kinetic model, indicating that the adsorption of the CR dye is primarily chemical adsorption. The Langmuir model fitted the experimental data with a maximum adsorption quantity of 248.22 mg/g. Besides, the adsorption capacity of prepared ZIF-9 still remained stable after three cycles. This strategy was a simple method compared to conventional methods in terms of reducing the amount of used solvents, energy requirements, and the duration of the synthetic process.